Migration drivers in carbonintensive regions in the EU - Stefan Jestl; Roman Römisch (The Vienna Institute for International Economic Studies (wiiw), 2023)
The paper analyses drivers of migration in carbon-intensive and non-carbon-intensive regions in the EU. Using a mix of econometric methods, such as spatial panel and spatial cross-sectional methods, as well as geographically weighted regressions on data for EU NUTS-2 and NUTS-3 regions, the results indicate that particularly carbon-intensive regions in Central and Eastern Europe are not only challenged by a potential decline in carbon-intensive employment but also by outward migration flows that could diminish their prospects for longer-term economic prosperity. From a policy point of view, the results indicate that policies focusing on the replacement of the lost jobs in carbon-intensive industries might not be enough for the carbon-intensive regions in Central and Eastern Europe. Instead, these regions need a simultaneous package of additional policies to improve their attractiveness.
Keywords: Q50; R11; R23; 330; carbon-intensive regions; green transition; regional migration